A Multi-Polarized Reconfigurable Plasma Antenna Array - Zhen Sun; Zhenzhen Zhou; Zhihao Tan; Huafeng Wu; Jiansen Zhao (International Journal of Antennas and Propagation)
Research on antenna reconfiguration is important in antenna applications. We present design of a multi-polarized plasma antenna with 40.68 MHz radio frequency (RF) power supplies and several discharge tubes filled with argon (neon) and mercury. Furthermore, self-made regulating circuits among the vibrators are introduced for the antenna array system. It can not only make the length of the dipole controllable but also improve the antenna gain and circular polarization (CP) performance under different lengths. Antenna arrays can be classified into linear and circular polarization by quickly adjusting the phase difference between vibrators. Both the experimental and simulation results indicate that the plasma antenna can realize impedance, pattern, and polarization reconstruction expediently. In addition, the linear polarization (LP) and CP can be transformed into each other quickly by adjusting the discharge conditions and regulating circuits. Moreover, compared with a symmetrical cross vibrator plasma antenna and a metal antenna of the same size, the proposed antenna array shows a certain gain and good reconfigurable performance within the frequency band of 150–250 MHz.